Studi Perilaku Harian Rusa Timor (Cervus timorensis) di Lembaga Konservasi PT Taman Satwa Semarang - Husna, Noora Lailatul; Kasiyati, Kasiyati; Djaelani, Muhammad Anwar; Setiawan, Hendrik Tri; Puri, Nur Liliana; Alrais, Aditya (Jurnal Sain Veteriner, 2024)
Adaptation of timor deer at the Conservation Institution of PT Taman Satwa Semarang is formed through a learning and memory process. The presence of visitors stimulates the deer to walk towards the side of the pen even though it is resting. Drop in feeding by keepers in the morning, afternoon, and evening causes the deer to become more active during the day. This study aims to analyze frequency and duration of the daily behavior of timor deer on weekdays with few visitors and on weekends with lots of visitors. Behaviors observed include moving, feeding, resting, grooming, aggressive, eliminative, and reproductive behavior. This research was conducted for 30 days. The object used in this study was a population of 18 adult timor deer. The method used is scan sampling, data recording of daily behavior which includes duration and frequency are carried out periodically at 10-minute intervals. The collected data includes daily behavioral, type of feed, as well as temperature and humidity. Data analysis was performed using t-test at a significance level of 5%. The results showed that visitor activity between weekdays and weekends had a significant effect (p˂0.05) on moving, feeding, resting, grooming, aggressive, and reproductive behavior. The conclusion of this study was the most timor deer perform resting and reproductive behaviors on weekdays, while moving, eating, and social behavior are mostly carried out on weekend.